IMMANUEL KANT'S PHILOSOPHICAL VIEWS ON EXISTENCE (Web of Teachers: Inderscience Research, 2024)
The article attempts to highlight the main aspects of I. Kant’s theory of knowledge, in which, in contrast to pre-Kantian philosophy, a new concept of a subject capable of cognitive activity has been put forward. Kant's provisions on the nature of the individual's active existence, the essence of the process of cognition as a synthesis of sensuality and reason, and the doctrine of antinomy are comprehended. The concept of a “transcendental subject”, the essence of Kant’s “criticism” as a method of cognition, experience as the main means of cognition are considered.